Blood, liver and rumen parameters of sheep fed diets containing detoxified castor bean meal - Menezes, Daniel Ribeiro; Costa, Roberto Germano; Araújo, Gherman Garcia Leal de; Pereira, Luiz Gustavo Ribeiro; Oliveira, Pablo Teixeira Leal de; Silva, Aldrin Ederson Vila Nova; Voltolini, Tadeu Vinhas; Moraes, Salete Alves de (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the blood, liver and rumen parameters, as well as to characterize and quantify the population of ciliated protozoa in the rumen of sheep fed diets with detoxified castor bean meal (DCBM). Thirty‑two lambs were used, for the evaluation of blood and liver parameters, and four rumen‑cannulated adult sheep were used to determine rumen parameters. The control diet was composed by buffel grass hay, ground corn grain, urea and soybean meal (SBM). In the treatments, SBM was partially replaced by DCBM at 15, 30 and 45% in the concentrate. There was no significant difference, among treatments, for the serum‑urea contents whose mean value was 666.0 mg L‑1. There was no significant difference, among diets, for glucose, aspartate aminotransferase and alanine aminotransferase, which had mean values of 690.3 mg L‑1, 127.4 IUL‑1 and 16.9 IUL‑1, respectively. The ammoniacal nitrogen and pH values had an increasing linear pattern with the replacement of SBM by DCBM. The genus Entodinium was the most frequent in all treatments and showed 76.4% overall mean of the total protozoa; the treatment without DCBM had the highest percentage of this genus among treatments. The diet substitution above 45% of soybean meal by the detoxified castor bean meal is favorable to the rumen environment.